2018
DOI: 10.1038/s41598-018-24483-z
|View full text |Cite
|
Sign up to set email alerts
|

Towards a generalized toxicity prediction model for oxide nanomaterials using integrated data from different sources

Abstract: A generalized toxicity classification model for 7 different oxide nanomaterials is presented in this study. A data set extracted from multiple literature sources and screened by physicochemical property based quality scores were used for model development. Moreover, a few more preprocessing techniques, such as synthetic minority over-sampling technique, were applied to address the imbalanced class problem in the data set. Then, classification models using four different algorithms, such as generalized linear m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 49 publications
2
75
0
Order By: Relevance
“…As illustrated in Fig. 4 of the preprocessing step, the input SMILES strings were preprocessed with onehot encoding [44][45][46], which sets only the correspond-ing symbol to 1 and others to 0. The input is truncated/padded to a maximum length of 100.…”
Section: Convolutional and Recurrent Neural Networkmentioning
confidence: 99%
“…As illustrated in Fig. 4 of the preprocessing step, the input SMILES strings were preprocessed with onehot encoding [44][45][46], which sets only the correspond-ing symbol to 1 and others to 0. The input is truncated/padded to a maximum length of 100.…”
Section: Convolutional and Recurrent Neural Networkmentioning
confidence: 99%
“…Also, Manganelli, Leone, Toropov, Toropova and Benfenati [115] designed a QSAR model that accurately predicts the human embryonic kidney cells (HEK293) response in the presence of 20 to 50 nm silica NPs. In another study based on the QSAR model and the 7 types of oxide NPs, it was shown that increasing the measured properties of NPs, especially the nanoparticle network model, the dosage, the enthalpy of formation, the exposure time and the hydrodynamic size, could increase the prediction level of the model by more than 90% [116]. The greater surface area of NPs results in their high chemical activity and subsequent enhanced reactive oxygen species (ROS) production causing oxidative stress, inflammation [117,118].…”
Section: Nps Interactions With Plasma Factors and Proteinsmentioning
confidence: 99%
“…Classification models for six different metal oxides and SiO 2 were presented in [57]. The authors compared the performance of four different algorithms: Generalized linear model, SVM, RF, and neural network.…”
Section: Metal Oxidesmentioning
confidence: 99%
“…The neural network model was identified as the model with the best predicting ability. The analysis of relative descriptor importance for the built neural network model identified dose, formation enthalpy, exposure time, and hydrodynamic size as the four most important descriptors [57]. However, the advantage of regression models for the analysis of toxicity of NPs was shown in comparison with the classification models on metal NPs and metal oxide NPs [58]: Regression models allow not only qualitative, but also a quantitative evaluation of the studied nanomaterials.…”
Section: Metal Oxidesmentioning
confidence: 99%